2016
DOI: 10.1128/jb.00747-15
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Bacteriophage Immunity through a Type I-E CRISPR-Cas System in Vibrio cholerae and Its Application in Bacteriophage Genome Engineering

Abstract: The classical and El Tor biotypes of Vibrio cholerae serogroup O1, the etiological agent of cholera, are responsible for the sixth and seventh (current) pandemics, respectively. A genomic island (GI), GI-24, previously identified in a classical biotype strain of V. cholerae, is predicted to encode clustered regularly interspaced short palindromic repeat (CRISPR)-associated proteins (Cas proteins); however, experimental evidence in support of CRISPR activity in V. cholerae has not been documented. Here, we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
115
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(124 citation statements)
references
References 53 publications
1
115
0
1
Order By: Relevance
“…The CRISPR-Cas system in strain O395 consisted of eight Cas proteins, a 2,407-bp CRISPR sequence comprised of a 28-bp repeat (GTCTTCCCCACGCAGGTGG GGGTGTTTC), and 39 unique spacer sequences (Table 1). This CRISPR-Cas system was shown to be a functional type I-E system that was confined to classical strains of V. cholerae (31). This system showed no homology to the CRISPR-Cas system identified here in RC385, and the integrase shared Ͻ27% (E value, 2eϪ32) amino acid identity with IntV1 from strain N16961, indicating they are unrelated.…”
Section: Figmentioning
confidence: 78%
See 2 more Smart Citations
“…The CRISPR-Cas system in strain O395 consisted of eight Cas proteins, a 2,407-bp CRISPR sequence comprised of a 28-bp repeat (GTCTTCCCCACGCAGGTGG GGGTGTTTC), and 39 unique spacer sequences (Table 1). This CRISPR-Cas system was shown to be a functional type I-E system that was confined to classical strains of V. cholerae (31). This system showed no homology to the CRISPR-Cas system identified here in RC385, and the integrase shared Ͻ27% (E value, 2eϪ32) amino acid identity with IntV1 from strain N16961, indicating they are unrelated.…”
Section: Figmentioning
confidence: 78%
“…In evolutionary terms, these data demonstrate that there is ongoing recombination and acquisition of CRISPR-Cas systems among closely related isolates and horizontal transfer among distantly related species. In support of this, a recent study showed that a type I-E CRISPR-Cas system could be transferred by natural transformation between V. cholerae isolates (31). A dynamic system would be expected in a region that is required for adaptive immunity to protect against constant attack from phages.…”
Section: Figmentioning
confidence: 92%
See 1 more Smart Citation
“…To test if LidI PLE 1 -mediated accelerated lysis is enough to impact diversity through the acquisition of random mutations in the resulting progeny phage population, we exposed PLE (-) V. cholerae with and without lidI PLE 1 to ICP1, collected the population of progeny phage, and looked for plaque formation on PLE (-) V. cholerae encoding a Type I-E CRISPR-Cas system endogenous to V. cholerae classical biotype strains engineered to harbor various anti-ICP1 spacers (Fig. 6C) (27). We see that for each spacer, fewer phages are able to overcome targeting in the phage progeny from lidI PLE 1 V. cholerae infections than the infections of strains without lidI PLE 1 (Fig.…”
Section: Lidi Ple 1 -+ -+ -+ -+mentioning
confidence: 99%
“…As no infectious ICP1 are produced, PLE activity ultimately defends populations of V. cholerae from ICP1 attack, functionally acting as an abortive infection system. In the face of this assault, ICP1 has acquired a functional Type I-F CRISPR-Cas adaptive immune system to target PLE in a sequence-specific manner, restoring ICP1 progeny phage production and overcoming PLE (24,27). While the full extent of ICP1, PLE, and V. cholerae interactions are unknown and continuing to evolve, efforts to understand how the PLE completely restricts ICP1 production have yet to identify any single PLE-encoded gene product that is necessary for inhibition, suggesting that multiple inhibitory strategies act synergistically to fully eliminate phage production (22,23,26).…”
Section: Introductionmentioning
confidence: 99%